Bronchoscopic Interventional Therapy Combined With Pembrolizumab in the Treatment of Pulmonary Large Cell Neuroendocrine Carcinoma: A Case Report - Yingyi Fan; Yingying Wang; Yanrong Ji; Shuang Li; Jian Zhang; Xingliang Hao (The Clinical Respiratory Journal)
ABSTRACT This study reports a significant clinical outcome following the use of bronchoscopic interventional therapy combined with pembrolizumab for treating pulmonary large cell neuroendocrine carcinoma (LCNEC), showcasing a novel approach in managing this aggressive cancer.